2005
DOI: 10.1002/asi.20134
|View full text |Cite
|
Sign up to set email alerts
|

Information problems in molecular biology and bioinformatics

Abstract: In this article we provide an overview of opportunities for research and practice in the domain of molecular biology by information and library scientists. We introduce the changing role of data and information in molecular biology, and how molecular biology is evolving from a technique-and technology-driven science to an information-driven science. We then describe the highlevel objectives of molecular biology and some broad classes of problems from an information perspective. We illustrate the high-level obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 89 publications
1
30
0
Order By: Relevance
“…Journal articles, conference proceedings, and books are prominent sources. Consistent with other previous studies [1,6,15] both groups of researchers and practitioners relied heavily on non-bibliographic information sources. Colleagues also emerged as a significant source of information for both MBB and CS participants since much of bioinformatics software development is a collaborative effort.…”
Section: Using Various Sources Of Informationsupporting
confidence: 90%
See 2 more Smart Citations
“…Journal articles, conference proceedings, and books are prominent sources. Consistent with other previous studies [1,6,15] both groups of researchers and practitioners relied heavily on non-bibliographic information sources. Colleagues also emerged as a significant source of information for both MBB and CS participants since much of bioinformatics software development is a collaborative effort.…”
Section: Using Various Sources Of Informationsupporting
confidence: 90%
“…For example, MacMullen & Denn's [6] research into information tasks of biologists revealed three categories: sequence alignment (i.e. sequences of DNA), structure prediction (i.e.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Best practices for implementing similar programs have been delineated (Badotti et al, 2013;Bednarski et al, 2005;Miskowski, Howard, Abler, & Grunwald, 2007;Via et al, 2011;Weisman, 2010), while others have discussed the programmatic role librarians can provide in supporting molecular biologists as they navigate the myriad data resources (MacMullen & Denn, 2005). Effective collaborations between librarians and the life sciences faculty have also been described in the literature (Bowden & DiBenedetto, 2001;Brown & Krumholz, 2002;Callinan, 2005;Dinkelman, 2010;Ferrer-Vinent & Carello, 2008;MacMillan, 2010;Winterman, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Molecular biologists are generally interested in the "functional aspect" of bioinformatics, such as analyzing data, discovering patterns, and developing methods of prediction for functions of organisms [6]. The computer scientists involved in this field mainly develop algorithms and information systems for storage, retrieval and analysis of biological data [7].…”
Section: Introductionmentioning
confidence: 99%